Infrared studies of the rutile surface - Griffiths, D.M. (1975)
The thesis describes infrared spectra recorded during the adsorption of water, acetone, acetic acid and hexifluaroacetone onto oxidized and reduced rutile, and the development of a technique for recording the infrared spectrum of a solid immersed in a liquid. Bands observed on the hydroxylated rutile surface have been assigned to hydroxyl groups on the (110) plane and water IrDlecules adsorbed onto strong and weak Lewis sites on all exposed planes. The hydroxyl groups exist as isolated or hydrogen bonded groups on surface titanium ions or as hydrogen ions on bridging oxygen ions. Reduction of the rutile surface considerably decreased the amount of rmlecular water adsorbed on the hydroxylated surface. The adsorption of acetone onto the hydroxylated surface took place in three consecutive stages, the first involved acetone molecules Lewis bonding to weak sites, the second resulted in the formation of mesityl oxide on strong surface sites and occurred with stage one in the absence of surface water molecules. In the third stage acetate molecules were formed as a result of the decomposition of mesityl oxide. Adsorption of acetic acid onto rutile resulted in the formation of water and arpeaxeme of bands due to acetate groups and Lewis-bonded co lexes on the weak sites. Hexafluoroacetone reacted with surface hydroxyls to produce a salt of the gem-diol hexifluoropropane-2,2-dio1, which decomposed on the removal of water to form trifluoroacetate species. An infrared cell has been developed enabling solid discs to be treated and inmiersed in a solution under inert conditions. The cell, of path length 0.7cm, has been used to study the adsorption of ether, from a solution in carbon tetrachloride, onto silica. Designs of variable path length cells for use Hexafluoroacetone reacted with surface hydroxyls to produce a salt of the gem-diol hexifluoropropane-2,2-dio1, which decomposed on the removal of water to form trifluoroacetate species. An infrared cell has been developed enabling solid discs to be treated and inmiersed in a solution under inert conditions. The cell, of path length 0.7cm, has been used to study the adsorption of ether, from a solution in carbon tetrachloride, onto silica. Designs of variable path length cells for use unier vacuum are included.